Temperature effects in composite structures of resonant frequency pressure sensor - Vtorushin Sergey; Talovskaya Alena; Barbin Evgenii; Kulinich Ivan (EPJ Web of Conferences)
The influence of temperature on the metrological parameters of measuring instruments is one of the primary challenges in their design. Temperature effects can introduce significant errors in measurements and also cause a reduction in sensitivity thresholds during operation. This article aims to investigate the response of a microelectromechanical pressure sensor with a resonant-frequency type transducer to temperature influence. This paper presents the results of studies on the impact of temperature fields on structural deformations and natural frequencies of composite resonators in a resonant-frequency microelectromechanical pressure sensor. The structure and functional features of the sensor under development are described, along with the phenomena occurring in the composite structure of resonators when exposed to a temperature field. Based on the research results, various resonator configurations were examined, designed as layered composite structures based on titanium and aluminum oxide. An analysis of their frequency characteristics was conducted, and options for reducing thermal stress effects in the composite layers were proposed.